Hybridization between yellow-billed cardinal paroaria capitata and red-crested cardinal P. Coronata in southern Argentina - Segura, Luciano Noel (2019)
The genus Paroaria is a group of conspicuous songbirds widely distributed in South America that has been studied recently to delimit its species and establish their phylogenetic relationships. Although hybridization has been reported between the most phylogenetically related species of the genus, we here present a case of hybridization between the Yellow-billed Cardinal (P. capitata) and Red-crested Cardinal (P. coronata) for the first time, two phylogenetically unrelated members of the group. This data contributes to the knowledge of this avian group whose systematics is still under debate.